Nursing-led management of side effects of radiation: evidence-based recommendations for practice - Poirier P (Dove Medical Press, 2013)
Patricia PoirierUniversity of Maine School of Nursing, Orono, ME, USAAbstract: It has been estimated that 50%–60% of patients diagnosed with cancer will receive radiation therapy at some point in their treatment. Although radiation therapy can play a significant role in the cure or control of cancer, and the palliation of symptoms, it also has side effects. Side effects of radiation therapy can interfere with patient quality of life and daily functioning. Severe side effects can lead to delays in treatment, potentially affecting the outcome of treatment. All patients receiving radiation therapy are at risk of fatigue and skin reactions in the area of the body being treated. Other side effects of radiation therapy are specific to the part of the body being treated. Radiation therapy to the head and neck area may cause oral mucositis, dryness, and nutritional deficiencies. Radiation therapy to the chest or lung area may lead to difficulty in swallowing and eating. Radiation therapy to the pelvis frequently causes diarrhea. There are many nursing interventions available to manage the side effects of treatment based on best available evidence and expert opinion. Nurses in all settings are essential in helping patients manage the side effects of treatment and maintain their quality of life. The purpose of this review is to provide nurses with evidence-based recommendations and suggestions for managing common acute side effects of radiation therapy.Keywords: evidence-based practice, radiation therapy, side effects, nursing management